Impact of Generic Entry on Hospital Antimicrobial Use: A Retrospective Quasi-Experimental Interrupted Time Series Analysis - Mercè Espona; Daniel Echeverria-Esnal; Sergi Hernandez; Alexander Almendral; Silvia Gómez-Zorrilla; Enric Limon; Olivia Ferrandez; Santiago Grau (MDPI AG, 2021)
Background: The impact of antimicrobials generic entry (GE) is controversial. Their introduction could provide an economic benefit yet may also increase their consumption, leading to a higher risk of resistance. Our aim was to analyze the impact of GE on trends of antimicrobial consumption in an acute-care hospital. Methods: A retrospective quasi-experimental interrupted time series analysis was conducted at a 400-bed tertiary hospital in Barcelona, Spain. All antimicrobials for systemic use for which a generic product entered the hospital from January 2000 to December 2019 were included. Antimicrobial consumption was expressed as DDD/100 bed days. Results: After GE, the consumption of cefotaxime (0.09, p < 0.001), meropenem (0.54, p < 0.001), and piperacillin-tazobactam (0.13, p < 0.001) increased, whereas the use of clindamycin (−0.03, p < 0.001) and itraconazole (−0.02, p = 0.01) was reduced. An alarming rise in cefepime (0.004), daptomycin (1.02), and cloxacillin (0.05) prescriptions was observed, despite not achieving statistical significance. On the contrary, the use of amoxicillin (−0.07), ampicillin (−0.02), cefixime (−0.06), fluconazole (−0.13), imipenem-cilastatin (−0.50) and levofloxacin (−0.35) decreased. These effects were noticed beyond the first year post GE. Conclusions: GE led to an increase in the consumption of broad-spectrum molecules. The potential economic benefit of generic antibiotics could be diluted by an increase in resistance. Antimicrobial stewardship should continue to monitor these molecules despite GE.